2020
DOI: 10.1177/1362168820976922
|View full text |Cite
|
Sign up to set email alerts
|

Representation of cultures and communities in a global ELT textbook: A diachronic content analysis

Abstract: This study examines the representation of cultures and communities in the world across five editions of New Headway elementary level textbook (NHE). It conducts a diachronic content analysis to explore how the representation of cultures and communities has evolved in NHE across five editions since its first edition’s publication in 1993. Adapting Kachru’s model of concentric circles for data analysis, we utilized Yuen’s adaptation of ACTFL’s (1996) standards for language teaching via the categories of persons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 52 publications
1
21
0
1
Order By: Relevance
“…We chose the level of books in line with Keles and Yazan's (2020) argument that introductory books are “likely to be the first formal English‐medium cultural resource for language learners” (p. 4). Moreover, because of our focus on images, we draw on the commonly held belief that lower‐level language learners tend to draw more on visual resources than higher‐level learners do (Risager, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose the level of books in line with Keles and Yazan's (2020) argument that introductory books are “likely to be the first formal English‐medium cultural resource for language learners” (p. 4). Moreover, because of our focus on images, we draw on the commonly held belief that lower‐level language learners tend to draw more on visual resources than higher‐level learners do (Risager, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…If a culture or group of people are misrepresented or underrepresented in a textbook, then a learner from that culture or group may become indifferent to the learning material (Anya, 2017). Alternatively, learners from different cultures or groups may fail to critically engage with it in terms of reflecting “on their own cultural values, meaning[s], and practices in relation to those of others” (Keles & Yazan, 2020, p. 4). In other words, a lack of inclusivity can lead to passive (transmissive) rather than active (transactional) modes of learning (see Gollnick & Chinn, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…From a curricular‐artifact viewpoint, Tomlinson and Masuhara (2013), for example, found that the six popular global coursebooks they analyzed reflected traditional language teaching views, with a strong emphasis on controlled practice and a weak communicative orientation. Likewise, scholars seeing textbooks as cultural artifacts have raised important concerns about the increasing presence of neoliberal discourses and values (Copley, 2018; Gray, 2012); the erasure of the working class (Gray & Block, 2014), different sexualities (Gray, 2013), and ethnic minorities (Toledo–Sandoval, 2020); and the overrepresentation of the white middle class (Dendrinos, 1992) and of inner circle cultures (Keles & Yazan, 2020)—all of which raise questions about the educational value of the content of these materials.…”
Section: Language Teacher Education and Language Teaching Materialsmentioning
confidence: 99%
“…Согласно концепции Т. А. ван Дейка, учебные пособия как ключевой жанр педагогического дискурса формируют знания людей о мире, общие социальные отношения, идеологии, основные нормы и ценности [Dijk 2001]. Подобного мнения придерживается и ряд зарубежных ученых [Canale 2022;Keles, Yazan 2020;Re-imagining… 2019]. Т. ван Леувен в качестве одной из задач учебников называет «сохранение эмоциональной "преданности" обучающегося» 1 [Leeuwen 1995: 86], а потому материал в них должен быть подобран и изложен таким образом, чтобы заставить реципиента дискурса чувствовать себя комфортно в процессе обучения.…”
Section: Introductionunclassified